A Review of Microneedles – Elevation to TDDS Approach and Function in Management of Psoriasis - Bodkhe, Saurabh Nandkisor; Kale, R. H.; Biyani, K. R. (Asian Journal of Pharmaceutical Research and Development, 2020)
Novel drug delivery system offers several advantages which could outweigh the benefits of other drug delivery system. The transdermal drug delivery system being one of them offers supremacy by by-passing the first pass metabolism which eventually helps in eradication of gastrointestinal irritation. The first patent for microneedles was field in 1970’s, researchers on utilizing microneedles as a drug delivery system has progress significantly. This review aims to provide background on microneedles, clinical benefits and function of microneedles. The microneedle method is much more superior to those traditional transdermal delivery ways because of advantage such as invasive painless, convenience and improves patient compliance. Every type of microneedles has different advantages according to their unique properties and designs. We developed a dissolving microneedle (MN) patch made of hyaluronic acid (HA) with excellent water solubility, biocompatibility and mechanical properties. The traditional therapeutic method is diverse embracing topical drugs, systemic drugs, physical therapy etc. with the limitation of present drug, the demand for new delivery method for psoriasis is in the spotlight. The major drawback of the transdermal drug delivery system is the hindrance created via skin into the systemic circulation. Thus in order to overcome this hurdle a replacement to this type of novel drug delivery system. One of the best pharmaceutical dosage form for those patients. They cannot take medicaments orally. TDDS established itself as an integral part of NDDS.